Meningkatkan Resiliensi Akademik Peserta Didik melalui Pendekatan Solution Focus Brief Counseling (SFBC) - Noviyanti Kartika Dewi; M. Ramli; Carolina Ligya Radjah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Online learning presents a major challenge for the world of education. One of the impacts that can be felt in learning from is the unpreparedness of the education system and stakeholders (teachers and students). The rapid change from face-to-face learning activities to online / online-based learning is a reality that inevitably must be faced. The unpreparedness of students in responding to changes related to online learning presents its own problems in the world of education. In online learning, students are given flexibility in designing their learning activities. The ability of students to be able to respond adaptively to difficulties encountered during online learning is called academic resilience. Academic resilience is one of the determining factors for the learning success of students. Therefore, it is important to realize that in this new normal era, counselors need to help students to improve their academic resilience through short solutions focused counseling services (Solution Focus Brief Counseling / SFBC). Solution Focus Brief Counseling (SFBC) is an alternative counseling service that counselors can choose to help students improve their academic resilience skills. The results showed that the SFBC approach was quite effective in helping students improve their resilience abilities. The SFBC approach is effective in helping students solve their problems because this approach in the process emphasizes more on the focus of the solution, not the problem. So that the counselee can be faster in finding a solution to the problem.